Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part V.-Pulps for Strawboards From Ulla Grass (Themeda arundinacea) and Panni Grass (Vetiveria zizanioides) - Bhat, R. V.; Singh, Man Mohan (Indian Forester, 1952)
There is a great disparity between the rated capacity and the production of strawboard mills in India due to the shortage of fibrous raw materials. Wheat and rice straws used for the production of these boards are not available to these mills in sufficient quantities as these are required for cattle fodder. Laboratory experiments carried out in this Branch have shown that pulps suitable for strawboards can be prepared from ulla grass ( Themeda arundinacea, Ridley, Syn. Anthistiria gigantia, Cav. ) and panni grass ( Vetiveria zizanioides, Stapf., Syn. Andropogon squarrosus, Hook. ) by digestion with lime. Since these grasses have no special use and are burnt down every year to prevent fires in forests, these should be available at cheap rates.